Actor problematic term between ancient and modern (Journal of the College of Education for Women, 2019)
Speech is associated with all early term grammar - somewhat - talking about the beginnings of the emergence of grammar, its foundation, and the truth is that this period has remained obscure, what came of them was a novels dealt with a facilitator beginnings as, and this means that what was of grammatical terms in the period of the first generation of grammarians do not constitute in itself, but the initial harbingers of serious way as in the science, and the real beginning of the term grammar mature as orally were at Hebron and Sibawayh evident in the book, then the efforts of the grammarians available until after the term of grammar arrived to what it is .In this area is (actor) a grammatical terminology, which won at the ancient scholars of the grammarians visual and Alkoviin fortunate than their care and that being the base engine for the reaction, P (actor) is already linked to a relationship predicate whether active truth or not the truth. It dealt Grammarians in active issues Fajtlfoa where (the issue of expressing elevated name after the envelope or neighbor and sewer) in the wholesale situational in such verse metrology Ng Ng ,some of them went to the (no doubt), an actor, to be adopted on the question, and some of them felt that tyro basing it on the basis of the grammarians to put the theory of the world, there is nothing to do with the sense that the speaker wants. The research then stop to discuss the perspectives that have emerged, including the views of those in this case being problematic from problems related to the term (actor) and lead to confusion and disorder for the concept, description and endoscopy. There are other issues that may be addressed research and discussion of what the offer came from the views of the scientists of the ancient and contemporary about this term and its considerations .There are researchers - such as Dr. Ahmad Mutawakil - those who believe that the name that begins with the nominal sentence is pregnant with the functions of the synthetic and semantic and deliberative carrier already own characteristics-based, and therefore be a possibility that is also called the term (actor); because both Debutante actor - in his view - holds the post (axis), a functional component assigns to signifier component self spokesman reported in wholesale as well as it constitutes the focus of talk which means that care and attention center, and went to him-Mutawakkil in a case launched two terms component and one in which a kind of confusion, a new problem; because you do not specify a term stability and disturbs the significance there and become chaotic in the use of common terms in linguistic studies of modern, it is true that the actor and debutante both datum him, except that the term varies according to location, this change requires synthetic properties related to wholesale in the course rhetorical. It is better to adopt a single term and no more in the naming of the name that begins with the nominal sentence, which the ancient scientists known as (Debutante), as well as the launch of the term (actor) on the name in the beginning of the speech lacks the verb, and not his appearance requires appreciation, it can not be there is an active non-reaction and vice versa, but does not appear on the surface level it is an object in the deep structure. As if al-Mutawakkil was launched here in the naming of this script as expressing the view that permits the name given to the verb in the sentence (active) is what went on him Albesrion it (tyro .)Jazz though harboring actor in the Arabic language may not be deleted; it represents the mayor to speak, has to stop searching when replies senior scientists Kelzimkhhari to delete metrology metrology metrology .And the inadmissibility delete actor among the ancients was the highlight of the motives and reasons that Dr. Ahmed al-Mutawakkil called to decide not to dispense with the function of the actor and the promise of the base component in the structure of convective consisting of (and a verb and effect) as well as the selected function as a component of Arabic sentence components performs the function of semantic (port) and one synthetic role (actor) and function of a deliberative (hub or focus), which limit the subject of any that plays an essential role in the incident, which refers to the mobile, as himself (actor) attribution to him semantic role (port) can not be assigned this semantic role to assign to the effect but only actor who leads the other semantic roles and at the forefront; because it is a source of implementation .Based on the progress made paths are going to search as follows :The first topic / overview of the initial term and concept inception and idiomatic .The second topic / actor problematic term when the ancients (visual and Alkoviin)صThe third topic / actor term problems with modern and Msmyate